Identifikasi Dan Komposisi Hasil Tangkapan Ikan Dengan Pancing (Hook Dan Line) Yang Didaratkan Di Desa Tanjung Luar, Lombok Timur - Hidayana, Siti Helis Pipi; Nuarsa, I Wayan; Negara, I Ketut Wija (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2024)
Tanjung Luar Village is a fishing village located in Keruak District, East Lombok Regency. The existence of this village is the center of local fishery production. Tanjung Luar fishermen mostly use boats to catch fish. The ships used are 2-5 GT in size. The fishing gear used by fishermen is fishing line. The purpose of this study was to determine the type of fish caught and the composition of the fish caught. This research was conducted for 2 months from March to May 2023 in Tanjung Luar Village. The data used is by direct observation in the field. Fish sampling was carried out using simple random sampling method with data analysis using the slovin formula to determine trips and identification books to identify fish caught. The results showed that the types of fish were grouped into 7 orders, 12 families and 14 genera dominated by the main types of fish caught using troll line, namely Skipjack with a percentage of the total catch of 56.3% and Tuna fish with a percentage of the total catch of 28.3%. Meanwhile, the main catch using hand line was grouper with 2.04% of total catch, 2.68% white snapper and 3.53% elder brother fish. By-catch that has an economic selling value is dominated by beard and moon fish with a total percentage of 0.22% and 0.56% respectively.